2010
DOI: 10.1080/11263504.2010.496199
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of small relic populations of silver fir (Abies albaMill.) in the northern Apennines

Abstract: Small and isolated silver fir populations from the Emilian Apennines (northern Italy) were studied to assess their level of genetic variation and their relationship with Alpine populations. We investigated the variability of two chloroplast microsatellites to analyse the within-population genetic variability of four peripheral and fragmented Apennine populations and to determine their phylogenetic relatedness to seven Alpine populations covering the entire distribution of silver fir in the Alps. Haplotypic ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 56 publications
2
20
2
1
Order By: Relevance
“…Evidence of different origins of the Apennine vs. Alpine populations has been reported for other conifers, e.g., for P. sylvestris and Abies alba Mill. (Piovani et al 2010). The remaining populations from the Alps belonged to different genetic clusters (G3 and G4), contrary to what was described by Heuertz et al (2010).…”
Section: Iforest -Biogeosciences and Forestrycontrasting
confidence: 50%
“…Evidence of different origins of the Apennine vs. Alpine populations has been reported for other conifers, e.g., for P. sylvestris and Abies alba Mill. (Piovani et al 2010). The remaining populations from the Alps belonged to different genetic clusters (G3 and G4), contrary to what was described by Heuertz et al (2010).…”
Section: Iforest -Biogeosciences and Forestrycontrasting
confidence: 50%
“…The APU population is of particular conservation value, since despite its very small size (only a few tens of individuals), it harboured a number of private alleles and showed no evidence of any bottleneck. Valuable populations like this, as pointed out by Piovani et al (2010), require careful management, which should include, for example, the cultivation of local seed. Overall, the diversity patterns revealed in the silver fir populations were consistent with the "rear edge versus leading edge" concept, which emphasizes the importance of peripheral populations for species survival and future adaptation to a changing environment (Hampe & Petit, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these populations are thought to be native, although some silver fir planting has been carried out in the past, especially in the northern Apennines. In particular, the populations sampled in MNR (Piovani et al, 2010), APU (Amorfini et al, 2004) and VER (Piovani et al, 2010;Ducci & Proietti, 1997) have been shown to have evolved naturally; in any case, only trees old enough (> 80 years) to have been in place prior to any recent afforestation activity were sampled. The populations from GOU, GOR, CHI, SAL, GBR, VIS, DOS, PAU, VER, ABE, FVP, ARC and GAR have been registered in the Italian National Book of Seed Stands: they were selected on basis of their phenotype and their health status (Morandini & Magini, 1975;Ducci & De Rogatis, 2010).…”
Section: Silver Fir Population Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In conseguenza di ciò, molte popolazioni di specie forestali sono caratterizzate da una elevata marginalità, sia in termini ecologici che puramente geografici (e.g. JuMP e PenuelAS, 2006;ScAlfi et al, 2009;PioVAni et al, 2010;leonArdi et al, 2012;de lAfontAine et al, 2013).…”
Section: In Questo Lavoro Viene Presentato Un Progetto DI Ricerca Volunclassified